Recent developments with rhodanine as a scaffold for drug discovery. (2nd December 2017) - Kaminskyy, Danylo; Kryshchyshyn, Anna; Lesyk, Roman
ABSTRACT: Introduction : Rhodanines, as one of the 4-thiazolidinones subtypes, are recognized as privileged heterocycles in medicinal chemistry. The main achievements include the development of drug-like molecules with numerous biological activities as well as approved drugs. Among rhodanines, 5-ene-rhodanines are of special interest, and are often claimed as pan assay interference compounds due to Michael acceptor functionality. Areas covered : Herein, the synthetic protocols for rhodanines and their transformation are reviewed. Biological activity is briefly discussed as well as biotargets, mode of actions and optimization directions. Furthermore, the utilization of 5-ene-rhodanines in Michael additions are discussed while both pro and contra arguments have been outlined within medicinal chemistry application. Expert opinion : Rhodanines remain privileged heterocycles in drug discovery. They are accessible building blocks for optimization and transformation into related heterocycles, simplified analogues and fused heterocycles with a thiazolidine framework. Michael acceptor functionality, as well as the thesis about low selectivity towards biotargets of rhodanines, must be confirmed experimentally and it cannot be based on just the presence of conjugated α, β-unsaturated carbonyl. Moreover, the positive aspects of Michael acceptors must be considered as well as their multitarget properties. New criteria for target affinity must be found. In conclusion, rhodanines are generally not problematic per se.